Promote Upgrade After-Sales Service Strategic Skills - Diyor Kholmamatov (Universitas Muhammadiyah Sidoarjo, 2019)
The article describes the importance of after-sales service in the field of wholesale marketing, the role in improving the competitiveness of goods in the wholesale trade in goods. There are opinions on the strategic directions of development of after-sales service in the wholesale trade. In conclusion, major points of the development have seen on the promotion of the after sales services and strategic skills.